2008
DOI: 10.1104/pp.108.116806
|View full text |Cite
|
Sign up to set email alerts
|

A Homolog ofScRAD5Is Involved in DNA Repair and Homologous Recombination in Arabidopsis  

Abstract: Rad5 is the key component in the Rad5-dependent error-free branch of postreplication repair in yeast (Saccharomyces cerevisiae). Rad5 is a member of the Snf2 ATPase/helicase family, possessing as a characteristic feature, a RING-finger domain embedded in the Snf2-helicase domain and a HIRAN domain. Yeast mutants are sensitive to DNA-damaging agents and reveal differences in homologous recombination. By sequence comparisons we were able to identify two homologs (AtRAD5a and AtRAD5b) in the Arabidopsis thaliana … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 64 publications
2
74
0
3
Order By: Relevance
“…As discussed above, uev1d (Wen et al, 2008) and rad5a (Chen et al, 2008) single mutants are sensitive to DNA damaging agents. Since genes involved in yeast DDT are conserved in Arabidopsis (Kunz and Xiao, 2007) and mammals (Pastushok and Xiao, 2004), it suggests that the two-branch model of DDT is also conserved; however, how DDT operates in plants is unknown prior to this study.…”
Section: Objective Of This Researchmentioning
confidence: 86%
See 4 more Smart Citations
“…As discussed above, uev1d (Wen et al, 2008) and rad5a (Chen et al, 2008) single mutants are sensitive to DNA damaging agents. Since genes involved in yeast DDT are conserved in Arabidopsis (Kunz and Xiao, 2007) and mammals (Pastushok and Xiao, 2004), it suggests that the two-branch model of DDT is also conserved; however, how DDT operates in plants is unknown prior to this study.…”
Section: Objective Of This Researchmentioning
confidence: 86%
“…While this investigation was in progress, Chen et al reported that only AtRAD5a (At5g22750), but not AtRAD5b (At5g43530), is required for the DNA damage response. More importantly, the Atrad5a Atrad5b double mutant behaves same as the Atrad5a single mutant (Chen et al, 2008), suggesting that AtRAD5b does not provide a backup function for AtRAD5a. This report prompted us to focus on the genetic interactions between TLS represented by AtREV3 and the putative error-free bypass pathway represented by AtRAD5a.…”
Section: Characterization Of Rad5a Rev3 Double Mutantsmentioning
confidence: 94%
See 3 more Smart Citations